Pengaruh Penerapan Sistem E-Filing dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi pada Kantor Pelayanan Pajak Pratama di Kota Sorong - Andi Uslaifatul Azizah; Wisang Candra Bintari; Retno Dewi Wijiastuti; Muhammad Ali (Prodi Manajemen STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of taxpayer awareness and implementation of the e-filing system on individual taxpayer compliance at the Pratama tax service office in Sorong City. The data of this study were obtained from a questionnaire (Primary) distributed to taxpayers who already have a taxpayer principal number and who have worked for more than one year using purposive sampling technique. The sample used in this study were 80 respondents with associative research methods and quantitative approaches. Before doing the research, the statements are first tested using validity and reliability. Then these results were analyzed using descriptive tests, instruments, classical assumptions, multiple linear regression techniques and hypothesis testing. The results of this study indicate that (1) Taxpayer Awareness has a positive and significant effect on the compliance of individual taxpayers. This is evidenced from the results of the determination coefficient test which has an R Square of 0.175 which means that the influence of taxpayer awareness and the application of the e-filling system on taxpayer compliance is 17.5%. (2) In the variable X1 the results of the t-test statistics have a significant value smaller than the level of significance, namely 0.001 <0.05, while in the X2 variable the t test results also have a small value, namely 0.001 <0.05, which means that the two independent variables have an influence. positive and partially syndicate on the dependent variable and each hypothesis of the dependent variable accepts H0 and rejects H1. (3). The results of the statistical f test have a significantly smaller value than the level of significant that is 0.004 <0.05, which means that the two independent relations have positive and significant effects simultaneously (simultaneously) on the dependent variable.